Peningkatan kemampuan komunikasi matematis dengan menggunakan pembelajaran berbasis masalah pada siswa sekolah menengah pertama - Jami, La; Suharna, Hery; Bakar, Marwia Tamrin; Lanani, Karman; Samura, Asri Ode (Mahesa Research Center, 2024)
This research examines the influence and improvement of students' mathematical communication skills using problem-based learning. The research design used a quasi-experimental quasi-experimental nonequivalent control-group design, a sample of 45 students. The instruments used are test questions in the form of essays. Data was obtained based on written test results, namely pretest and posttest data. The analysis uses parametric t-test statistics. The results show that problem-based learning can influence mathematical communication skills in the low category. The effect of problem-based learning is minimal. Problem-based learning can improve students' mathematical communication skills in the low category.